Two new taxa of brush-footed butterflies (Lepidoptera: Nymphalidae) from the Western Ghats biodiversity hotspot, southern India - Kunte, Krushnamegh; Basu, Dipendra Nath (Zootaxa, 2024)
A new species, Amathusia travancorica sp. nov. (Nymphalidae: Satyrinae: Amathusiini), and a new subspecies, Athyma inara sahyadriensis ssp. nov. (Nymphalidae: Limenitidinae: Limenitidini), are described from the Western Ghats biodiversity hotspot, India, based on multiple male and female specimens. The new taxa are compared with type specimens of related species and subspecies, revealing consistent differences that distinguish the new taxa. Genitalia dissections are also provided as comparative materials. Additional information is provided on historical records, distributional ranges, habits and habitat, phenology, larval host plants, and early stages. Finally, the type locality and synonymy of Pantoporia mera Swinhoe, 1917 are discussed based on comparison of type specimens (Pantoporia mera Swinhoe, 1917 syn. nov.=Athyma inara Westwood, 1850).